Factors that Affect the Practice, Implementation, Compliance and Culture of Occupational Safety and Health in Institute of Technical and Vocational Education in the Malaysia - Isa, Rosidi Fahlid Mohd; Azman, Mohamed Nor Azhari; Oduh, William Akporobaroh (International Journal of Psychosocial Rehabilitation, 2020)
In Malaysia, generally, the awareness of occupational safety and health has shown an impressive improvement over the years. However, this condition does not guarantee a satisfactory level of occupational safety as the rate of accidents among workers is still at a high level throughout the years. As a result, this research is conducted to evaluate the occupational safety and health practices among students and lecturers of Technical and Vocational Education and Training Institutions (TVET) in Malaysia from the view of the practice, implementation, compliance and culture level of safety and health practices. The methodology of this research is using a quantitative approach. This study is carried out in two parts, Part A is about the respondents’ personal information and Part B is a survey by using a questionnaire with respondents from several institutions of Technical and Vocational Education such as Vocational College (KV), Industrial Training Institute (ILP), National Youth Skills Institute (IKBN) and Mara Skills Institute (IKM). Descriptive statistics tests are used to describe occupational safety and health practice, implementation, compliance, and culture. Hence, this research found that the level of practice and safety applied it at a high level. This means that almost all students and lecturers agree that occupational safety and health practices are very important to be adhered to and practiced. The culture of safe practices will creates a safe working culture, that indirectly create a safety culture. Thus, it will become an organisation that provides a safe environment and give benefit to the workers’ activities